Evaluation of alumina toughened zirconia implants with a sintered, moderately rough surface: An experiment in the rat. Issue 1 (January 2016) - Kohal, Ralf J.; Bächle, Maria; Renz, Alexander; Butz, Frank
Abstract: Objective: Alumina toughened zirconia (ATZ) is more fracture resistant than unmodified zirconia and has been shown to be a viable substrate for the growth of osteoblasts. In this study, we examined the histological and biomechanical behavior of moderately roughened ATZ implants in rat femoral bone. Methods: Miniature implants made of ATZ with pore-building polymers sintered onto the surface and electrochemically anodized titanium (TiUnite ® ) were placed into the femurs of Sprague-Dawley rats. Implant surface topography was analyzed by 3D laserscan measurements and scanning electron microscopy (SEM). After a healing period of 14 and 28 days, respectively, histologic and biomechanical testing was performed. Results: Under the SEM, the TiUnite ® surface could be clearly distinguished from the ATZ surface, but 3D laserscan measurements indicated a moderately rough surface topography for both, TiUnite ® ( S a = 1.31 μm) and ATZ ( S a = 1.51 μm). The mean mineralized bone-to-implant contact showed the highest values after 14 and 28 days for TiUnite ® (58%/75%) as compared to ATZ (24%/41%). The push-in values after a healing period of 14 and 28 days, respectively, increased from 20 N to 39 N for TiUnite ® and from 10 N to 25 N for ATZ. Significance: Our findings suggest that the moderately roughened ATZ implant surface is well accepted by rat bone tissue. However, compared to titanium, the osseointegration-process of ATZ seems to proceed more slowly in that early phase of implant integration.